Audit of the Efficiency of the Use of State (Municipal) Property - I. V. Lipatova; D. V. Antipova (Учёт. Анализ. Аудит)
The article is devoted to the problem of organizing and conducting an audit of the efficiency of use of state (municipal) property. The relevance and expediency of carrying out control and expert-analytical activities in the form of an audit of the efficiency of use of state (municipal) property is substantiated. The methodological basis of the study includes consideration of the structure of state (municipal) property, the activities of the Accounts Chamber of the Russian Federation, the Moscow Chamber of Control and Accounts, as well as the activities of the Federal Agency for State Property Management. The purpose of the study is to develop proposals for the development of control and expert-analytical activities in the form of performance audit of the use of state (municipal) property. In the course of the study the following methods of scientific research were applied: synthesis, analysis, generalisation, conversation and interview, comparison, description. Possible control and expert-analytical procedures within the framework of reporting and performance auditing are presented. The characteristics of possible violations encountered by state control and audit bodies are given. Problematic aspects associated with the management and use of state (municipal) property and with the implementation of an audit of the efficiency of use of state (municipal) property have been identified. As a result of  the analysis of the practice of organizing and conducting an audit of the efficiency of use of state (municipal) property, recommendations regarding the identified problems are presented. The results in the form of recommendations for solving the identified problems can be useful to the relevant departments of the Accounts Chamber and the Ministry of Finance of Russia: the Department of Revenue Audit of the Accounts Chamber and the Department of Regulation of Property Relationships.